Four magnetic resonance imaging surveillance-detected breast cancer cases in cancer-free BRCA1/2 mutation carriers - Megumi Takaoka; Shozo Ohsumi; Yuichiro Miyoshi; Mina Takahashi; Seiki Takashima; Kenjiro Aogi; Teruhiko Shimizu; Norihiro Teramoto; Yasuko Yamamoto; Miki Okamura (Surgical Case Reports, 2021)
Abstract Background Hereditary breast and ovarian cancer (HBOC) syndrome is a susceptibility syndrome for cancers, such as breast and ovarian cancer, and BRCA1/2 are its causative genes. Annual breast-enhanced magnetic resonance imaging (MRI) is recommended for BRCA1/2 mutation carriers aged over 25 years as a secondary prevention of breast cancer. However, breast MRI surveillance is rarely performed in Japan, and only four cases of breast cancer diagnosis triggered by MRI surveillance have been reported. Case presentation At our hospital, MRI triggered the diagnosis of breast cancer in four cancer-free BRCA1/2 mutation carriers. In one of our four cases, although MRI showed only a 3-mm focus, we could diagnose breast cancer by shortening the surveillance interval considering the patient’s high-risk for developing breast cancer. Conclusions Image-guided biopsy, including MRI-guided biopsy, depending on the size of the lesion, and shorter surveillance intervals are useful when there are potentially malignant findings on breast MRI surveillance for cancer-free patients with HBOC.